The HUBUNGAN TINGKAT KECANDUAN SMARTPHONE DENGAN PERILAKU AGRESIF PADA REMAJA: HUBUNGAN TINGKAT KECANDUAN SMARTPHONE DENGAN PERILAKU AGRESIF PADA REMAJA - Aisyah Nur Octa Paraga; Yulian Wiji Utami; Niko Dima Kristianingrum (Jurnal Keperawatan Terapan, 2025)
Adolescents are the biggest users of smartphone in accessing the internet, spending at least 3 hours more in using smartphone. This phenomenon has caused adolescents addicted to smartphone. Addictive behavior of smartphone in adolescents has a serious impact on health, such as tendency of aggressive behavior. This study aims to determine the relationship between the level of smartphone addiction and aggressive behavior in adolescents. This study employs quantitative research with a cross-sectional approach. The study included 245 adolescents, with data collection techniques using multistage sampling. The data was collected using the Smartphone Addiction Scale Short Version (SAS-SV) questionnaire and the Buss Perry Aggression Questionnaire (BPAQ) with the Spearman Rank correlation test. The results of data analysis obtained a p-value (0.001) < ? (0.05) and r = 0.210, with a positive relationship direction which means that the higher the level of smartphone addiction is, the higher the aggressive behavior in adolescents is. The study concludes that there is a relationship between the level of smartphone addiction and aggressive behavior. This study recommends that further researchers are expected to examine other factors or efforts aimed at reducing the level of addiction to smartphones and efforts to reduce aggressive behavior, especially for adolescents.